Efeito da terapia por fotobiomodulação no controle da lesão articular em modelo experimental de artrite reumatoide – aspectos morfológicos e funcionais - Santos, Solange Almeida dos (2020)
Rheumatoid Arthritis (RA) is a chronic, autoimmune, inflammatory, progressive disease that leads to irreversible destruction of cartilage and bone. Experimental in vivo studies using photobiomodulation therapy have demonstrated positive effects on the modulation of the inflammatory process. Objective: To analyze the effects of photobiomodulation therapy on cell organization and the mechanical properties of knee cartilage in an experimental model of Rheumatoid Arthritis induced by type II Collagen. Methodology: A pilot study with 12 animals was carried out to determine the parameters of Collagen II and Freund's Adjuvant for RA induction. In the second phase of the study, twenty-five male wistar rats were divided into 5 groups, CTL (control), RA (rheumatoid arthritis) with 7 days (AR7) and 14 days (AR14), in addition to the groups treated with PBM in 7 days (AR7 + PBM) and 14 days (AR14 + PBM). For RA induction, the animals received 2 intradermal injections of the lesion-inducing solution on days 0 and 7 and after 21 days a 3rd dose was applied to the knee joint. For the treated groups, PBM (808nm; 2J; 50mW) started on the 21st, immediately after the last induction. Results: A reduction in Rupture Force (Fracture) and maximum Deformation (Dmax) was observed in RA groups, in addition to histological changes such as tissue disorganization and the presence of inflammatory infiltrate. PBM reduced the biomechanical changes caused by RA and promoted better histological organization, preventing the progression of the disease. Conclusion: The model of RA induction using Collagen II and Freund's Adjuvant with 1st and 2nd intradermal induction and 3rd knee induction was effective in inducing RA with clinical signs characteristic of the disease. PBM improved the morphological and functional characteristics, reducing the impact on cartilage resistance and tissue organization. PBM appears as an important therapy in the treatment of RA with no known side effects.